2020
DOI: 10.1016/j.pmedr.2020.101214
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors related to participation in general health checkup and survey of the effect of low-dose radiation exposure on health of residents of Fukushima Prefecture after the Fukushima Daiichi nuclear power plant accident

Abstract: Highlights Health literacy was lower in Fukushima Prefecture residents after the radiation accident. Educational background in participants may be associated with low health literacy. Health literacy wasn’t associated with checkup and radiation survey participation. Low radiation anxiety was positively associated with participation in checkup. A longitudinal study is needed to clarify if anxiety affects checkup partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
4
1
10
Order By: Relevance
“…Moreover, we found that socioeconomic variables such as unemployment and household assets were significantly related to health check-up behavior, whereas university degree and household income were not. For the unemployment variable, a significant and positive link with health check-up behavior was an unexpected finding, as it did not align with many other studies [ 8 , 61 , 62 ]. One justification for this may be that as our study excludes those participating in mandatory health check programs organized at school or work, all other non-mandatory forms of health check-ups would be greatly accessible to unemployed people, because they would have more time and energy.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, we found that socioeconomic variables such as unemployment and household assets were significantly related to health check-up behavior, whereas university degree and household income were not. For the unemployment variable, a significant and positive link with health check-up behavior was an unexpected finding, as it did not align with many other studies [ 8 , 61 , 62 ]. One justification for this may be that as our study excludes those participating in mandatory health check programs organized at school or work, all other non-mandatory forms of health check-ups would be greatly accessible to unemployed people, because they would have more time and energy.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition to health literacy, the study also reported that low education level was positively associated with current smoking compared with high education level 11 . Additionally, previous studies reported a significant association between education level and health literacy 22,23 . In this context, further research is necessary to clarify the association between health literacy and current smoking in various countries and regions, stratified by education level.…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies have reported that there is a negative relationship between anxiety about radiation and participation in health checkups, and that managing radiation anxiety may be important for improving the health of the population after the FDNPP accident [29]. It is possible to explain the low medical exposure due to chest radiography using the radiation dose scale shown in figure 1, and publishing FAQs [8] on radiation for the general public may further help alleviate anxiety.…”
Section: Discussionmentioning
confidence: 99%